2017
DOI: 10.22587/ajbas.2017.11.13.3
|View full text |Cite
|
Sign up to set email alerts
|

Cloud Computing Adoption by Business Organization: A Systematic Review

Abstract: Background: Cloud computing is a new technology that can provide benefits to all stakeholders. Most of the studies attempted to find the factors that affect the adoption of this technology. However, the findings of these studies still inconclusive. In addition, the theoretical models that are used are varied. Therefore, the purpose of this paper is to review, integrate and consolidate the literature to identify the factor that affect the adoption of cloud computing by business organization. Objectives: The obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Awareness of knowledge refers to the organization's prediction, interpretation, and comprehension of the importance and possibility of adoption of technology. As revealed by Alatresh et al (2017), several studies attempted to describe the factors impacting business organizations' of cloud computing considering the framework utilized in understanding computing, TAM (Technology Acceptance Model)is the most significant structure used. It was suggested that awareness should be part of the implementation development to facilitate the incorporation of cloud-based computing in everyday business operations.…”
Section: Cloud Computing Implementation Csfs Categoriesmentioning
confidence: 99%
“…Awareness of knowledge refers to the organization's prediction, interpretation, and comprehension of the importance and possibility of adoption of technology. As revealed by Alatresh et al (2017), several studies attempted to describe the factors impacting business organizations' of cloud computing considering the framework utilized in understanding computing, TAM (Technology Acceptance Model)is the most significant structure used. It was suggested that awareness should be part of the implementation development to facilitate the incorporation of cloud-based computing in everyday business operations.…”
Section: Cloud Computing Implementation Csfs Categoriesmentioning
confidence: 99%
“…If the cloud provider does not offer the management of event logs, then it is almost impossible to track the affected resource or data [12] Before taking services, check what type of event log services CSP provides…”
Section: Cloud User (Cu)mentioning
confidence: 99%
“…If data breach situation has occurred, then inform all the possible clients for that [12] User -Interoperability-if the CU has any problem or dissatisfaction with vendor, then there should be a flexibility to migrate from one vendor to another. But generally, they face vendor lock-in problem -Trust between CU and CSP-the CU should have trust on CSP that he is giving secure services with all security measures.…”
Section: Cloud User (Cu)mentioning
confidence: 99%